Shifting role of parenting from Mom’s to Dad’s : a case study of a Mix Culture Families - Wulandari, Yenie (Jurnal Teori dan Praksis Pembelajaran IPS, 2022)
The discourse on the impact of the COVID-19 pandemic tends to focus on the health and economic aspects. Even though the secondary impact of this pandemic has also resulted in conflicts of cultural values. This qualitative study tried to get a comprehensive picture related to the dynamics of their shifting role of parenting and its impact on their children. This study used social role theory, social judgment theory, and social exchange theory. The subjects were three inter-ethnic married couples: Javanese-Minang, Bantenese-Madurese, and Javanese-Sundanese in Banten province, Indonesia. This research used data collection techniques through in-depth interviews and stays for one month with each family. The result showed that although the parents did not affect by society's judgment through their acts there was a tendency to impact the child's development after they were reaching their teenage years.